Demographic Characteristics of Fruit Sellers and Chemical Preservation Practices in Birnin Kebbi, Nigeria - Yahaya, Tajudeen; Faruk, Mohammed Umar; Abdulazzez, Abdulmalik (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Fruits in Birnin Kebbi, Nigeria, are often preserved using chemicals to extend their shelf life, maintain freshness, and enhance quality and taste. However, global concerns persist about the safety of these preservatives, particularly when applied indiscriminately. This study aimed to determine the demographic characteristics of fruit sellers in Birnin Kebbi and the preservatives they commonly use. Structured questionnaires were administered to 200 participants who provided informed consent. The results showed that 116 (58%) of the respondents were male, while 84 (42%) were female. Most participants (38%) were aged 18–25 years (76 individuals), followed by those aged 26–35 years (60 individuals, 30%). A significant proportion of participants (82; 41%) had no formal education, while 48 (24%) had primary education. The majority of participants (120; 60%) belonged to the Hausa ethnic group, and 156 individuals (78%) identified as Muslims. Marital status was evenly distributed, with 84 participants (42%) being single and 80 (40%) married. Regarding fruit preservation practices, watermelon was the most frequently preserved fruit, cited by 50 participants (25%), followed by oranges (42; 21%) and bananas (22; 11%). Among chemical preservatives, sulfite was the most commonly used, reported by 84 (42%) participants, followed by citric acid (36; 18%), sodium benzoate (28; 14%), calcium chloride (24; 12%), benzoic acid (18; 9%), and ethanol (10; 5%). Alarmingly, 95% of participants demonstrated inadequate knowledge of proper preservative application methods, raising concerns about potential health risks for consumers. These findings suggest that fruit preservation practices in Birnin Kebbi may expose consumers to health hazards. It is imperative to educate fruit sellers and consumers on the safe use of chemical preservatives, including appropriate concentrations and application techniques, to mitigate these risks and promote safer fruit consumption.